Protein and energy requirements in Mediterranean species - Lupatsch I. (Mediterranean fish nutrition, 2005)
A novel approach to determine the protein and energy requirements in fish is described: this involves quantifying the requirements for energy and protein as the sum of the daily requirements for maintenance and growth. The requirement for maintenance is mainly a function of the size of the fish as well as the water temperature, and is proportional to the metabolic body weight. The requirement for growth depends on the weight gain and its energy and protein content. Total daily intake can therefore be calculated by incorporating the respective utilization efficiencies of energy and protein deposits. The consequence of this approach is that protein and energy needs are expressed in terms of absolute daily intake per unit of anticipated weight gain and not only as an inclusion level in the diet. Protein and energy requirements can thus be calculated for seabream and seabass at various stages of their growth.
Workshop on Mediterranean Fish Nutrition, 2002/06/01-02, Rhodes (Greece)